Hydrogel Preparation from Shrimp Shell-Based Chitosan: The Degree of Crosslinking and Swelling Study - Dhena Ria Barleany; Jayanudin Jayanudin; Nasihin Nasihin; Mela Widiawati; Meri Yulvianti; Denni Kartika Sari; Akbar Gunawan (ASEAN Journal of Chemical Engineering, 2023)
Chitosan is a natural polymer derived from different starting materials such as fish scales, crab and shrimp shells. Due to the advantages like biocompatibility and biodegradability, chitosan has been widely used in hydrogel development. This current study aims to make chitosan from shrimp shells, synthesize hydrogel from chitosan, and observe the effect of various chitosan preparation treatments on the properties of the hydrogel. The preparation of chitosan was carried out through demineralization, deproteinization, and deacetylation process. HCl concentration during demineralization and NaOH concentration during deproteinization were varied (1; 1,5; 2) M and (1; 1,5; 2) M, respectively. Chitin deacetylation was conducted using 60% (w/v) of NaOH at the temperature of 90oC for 120 min, and chitosan was resulted. Chitosan based hydrogel was then synthesized with the addition of alginate and glutaraldehyde. The effect of HCl and NaOH concentrations during demineralization and deproteinization on the deacetylation degree of chitosan was observed. The effect of deacetylation degree of chitosan on the degree of crosslinking and swelling property of the hydrogel were also evaluated. Chitosan resulted from this study has the optimum degree of deacetylation at 57.28 %, resulting from demineralization by using HCl 2M and deproteinization with NaOH2 M. Higher deacetilation degree of chitosan causing the increase of the degree of cross-linking and decrease of the swelling capacity of the hydrogel. The highest degree of cross-linking is 78.85 %, and the swelling capacity is 47 %.